Contemporary issues in Islam - Afsaruddin, Asma, 1958- (Edinburg: Edinburg University press, 2015)
Asma Afsaruddin explores how Islamic concepts have evolved and transformed over time, both in how they are defined and how they are applied. Afsaruddin follows certain concepts, like jihad (holy war) and shahada (martyrdom), and explains how they have been understood in different historical circumstances. By analysing biographical dictionaries from different times, such as Ibn Hajars in the 14th century, she plots the changes in how society viewed womens roles. And she investigates the historicity of claims made by Islamists today that their version of political Islam goes back to the first century of Islam by surveying early historical, political and hadith works.
Includes bibliographical references (pages 209-216) and index.
Keywords: 2000 - 2099; Islam -- 21st century; Islam and politics; Islam; Islam and politics; Islam; Islamitisch recht; Heilige oorlog; Kalifaten